URGENSI PEMERINTAH KABUPATEN/KOTA MENDIRIKAN BPR SYARIAH - Temmy Wijaya (Nurul Jadid University, 2019)
The purpose of this study is to analyze the urgency of the Regency / City Government in Indonesia to establish a Sharia Rural Bank in the era of regional autonomy in order to improve the standard of living of the people and increase the receipt of Regional Original Revenues (PAD). Before the birth of Sharia Rural Banks in Indonesia, the public was first familiar with the People's Credit Bank (BPR). According to Law No. 21 of 2008 stated that BPR is a conventional bank that in its activities does not provide services in payment traffic. Where conventional BPRs still apply interest systems in their operations.Sharia Rural Bank (BPRS) is a bank that conducts business activities based on Sharia principles in which its activities do not provide services in payment traffic. Law (UU) No. 21/2008 concerning Sharia Banks has specifically regulated the existence of Sharia Banks in Indonesia. The law complements and perfects Law No. 7 of 1992 concerning Banking as amended by Law No. 10 of 1998 which has not been specific so it needs to be specifically regulated in a separate Act. According to Article 18 of Law No. 21 of 2008, Sharia Banks consist of Sharia Commercial Banks and Sharia People Financing Banks.There are several objectives expected from the establishment of Sharia Rural Banks in the economy, especially in the regions (Regency / City), which are as follows:1. Improving the economic prosperity of Muslims, especially those in economically weak groups who are generally located in rural areas.2. Increase employment, especially at the sub-district level so as to reduce the flow of urbanization.3. Fostering the spirit of ukhuwah Islamiyah through economic activities in order to increase income per capita towards an adequate quality of life.4. To accelerate the rotation of economic activity, especially the real sector in the regions